Fire Regime in a Peatland Restoration Area: Lesson from Central Kalimantan - Bekti Larasati; Mamoru Kanzaki; Ris Hadi Purwanto; Ronggo Sadono (Fakultas Kehutanan Universitas Gadjah Mada, 2019)
Peat fires have caused carbon emissions and damage to local and regional communities in Indonesia. An effective fire prevention system is required for mitigating climate change and enabling sustainable development of peatlands. This study examined the fire regime in a peatland restoration area in Central Kalimantan in order to assist the establishment of a fire prevention system. The fire regime was analysed using spatial-temporal analysis, land cover change mapping, and logistic regression analysis. Spatial-temporal analysis was done using monthly Niño 3.4 sea surface temperature anomalies, daily rainfall, and MODIS Active Fire (MCD14DL) hotspots from 2006 to 2015. Land cover change was mapped using Landsat imagery from2014, 2015 and 2016. Logistic regression analysis was conducted to identify significant factors that increase fire risk. The temporal analysis showed that the strongest El Niño occurred in 2015, when the region experienced a 140-days drought period. The highest number of hotspots was also observed in this year, with hotspots concentrated in the latter half of drought period. Moreover, spatial analysis using Kernel Density Estimation (KDE) showed fire recur in degraded areas. The logistic regression analysis used topographic and proximity factors, land cover classes, and soil types as independent variables. It showed that fire in 2014 and 2015 was associated with several land cover classes and was related to historical fire occurrence areas based on KDE results. Several area of peatland forests burned in 2015 and occurred at the forest edge areas located near cultivated or degraded land (e.g. shrubland) and oil palm plantations. Based on the results, the fire regime in the study area is characterized by fires that occurring/recurring in relation to climatic conditions, especially drought periods, and are typically located in cultivated or degraded land cover classes. These parameters should be considered in developing a fire prevention system in the restoration area.Rezim Kebakaran Hutan dan Lahan di Area Restorasi Lahan Gambut: Studi dari Kalimantan TengahIntisariKebakaran di lahan gambut menyebabkan emisi karbon dan kerusakan sistem kehidupan masyarakat lokal dan regional. Sistem pencegahan kebakaran yang efektif diperlukan untuk mitigasi perubahan iklim serta mendorong pembangunan lahan dan hutan yang lestari di kawasan gambut. Studi ini meneliti tentang rezim kebakaran hutan dan lahan di suatu kawasan restorasi gambut di Kalimantan Tengah. Rezim kebakaran hutan dan lahan dianalisis menggunakan analisis spasial-temporal, perubahan tutupan lahan, dan regresi logistik. Analisis spasial-temporal menggunakan parameter nilai rata-rata sea surface temperature (SST) bulanan, curah hujan harian, dan hotspot dari MODIS Active Fire (MCD14DL) tahun 2006-2016. Perubahan tutupan lahan dipetakan dengan analisis citra Landsat tahun 2014, 2015 dan 2016. Regresi logistik digunakan untuk menganalisis faktor yang berpengaruh pada peningkatan resiko kebakaran. Analisis temporal terhadap nilai SST tahun 2006-2016 menunjukkan bahwa El- Niño terparah terjadi di tahun 2015 yang memiliki hari tanpa hujan selama 140 hari berturut-turut dan ditemukan titik hotspot terbanyak. Kernel Density Estimation (KDE) digunakan dalam analisis spasial dan hasilnya menunjukkan bahwa kebakaran terjadi dan dapat berulang di area terdegradasi. Regresi logistik menggunakan parameter yang terdiri faktor topografis, kedekatan dengan sungai/kanal, tipe penutupan lahan, serta jenis tanah. Hasil analisis menunjukkan bahwa kebarakan tahun 2014 dan 2015 berhubungan dengan beberapa tipe tutupan lahan di area yang secara historis pernah terbakar berdasarkan analisis KDE, sehingga area tersebut terindikasi telah terdegradasi sebelumnya. Beberapa area hutan di lahan gambut juga mengalami kebakaran pada tahun 2015 khususnya di area tepi hutannya. Berdasarkan hasil, rezim kebakaran di area studi dapat dijelaskan bahwa kebakaran terjadi dan dapat berulang karena pengaruh iklim.